Про доцільність розгляду гідромеханічних процесів з урахуванням сил поверхневого натягу на границі контакту тверде тіло - рідина - Білонога, Ю. Л. (НТУ "ХПІ", 2006)
The article presents a scientific concept of examination of the hydraulic-mechanical processes of liquid flows in the pipeline, deposition considering surface tension forces in lam-inar (L) border layer on the contact border solid body-liquid. Domination of Euler criterion and surface criterion is demonstrated based on comparison of the similarity criteria in L-layer. Number of dependences for calculation of the L-layer thickness is demonstrated in conditions of liquid flows in pipelines and deposition of solid particles in liquid medium.
Keywords: тверде тіло; рідина; гідромеханіка; поверхневий натяг; трубопровід